2016
DOI: 10.4014/jmb.1607.07073
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Pseudostellaria heterophylla with Quorum Sensing and Quorum Quenching Bacteria Mediated by Root Exudates in a Consecutive Monoculture System

Abstract: Many plant-pathogenic bacteria are dependent on quorum sensing (QS) to evoke disease. In this study, the population of QS and quorum quenching (QQ) bacteria was analyzed in a consecutive monoculture system of . The isolated QS strains were identified as with -type QS system and exhibited a significant increase over the years of monoculture. Only one QQ strain was isolated from newly planted soil sample and was identified as, which secreted lactonase to degrade QS signal molecules. Inoculation of to root could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 34 publications
(55 reference statements)
1
10
0
Order By: Relevance
“…The results showed that numerous bacteria in soil were detected as QS bacteria, accounting for 32.5% of all randomly selected strains in the NP soil and 17% in the diseased soil. This observation is consistent with the findings in previous studies that QS systems are widespread among the bacterial populations in the phytosphere (Veselova et al, 2003;Zhang et al, 2016). Molecular identification found that the QS bacteria isolated from the healthy NP soil mainly consisted of Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results showed that numerous bacteria in soil were detected as QS bacteria, accounting for 32.5% of all randomly selected strains in the NP soil and 17% in the diseased soil. This observation is consistent with the findings in previous studies that QS systems are widespread among the bacterial populations in the phytosphere (Veselova et al, 2003;Zhang et al, 2016). Molecular identification found that the QS bacteria isolated from the healthy NP soil mainly consisted of Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 93%
“…and stimulate certain pathogenic bacteria and fungi (Wu et al, 2016c;Chen et al, 2017). Zhang et al (2016) also demonstrated that both root exudates and tuberous root extracts of P. heterophylla could significantly promote the growth of S. marcescens, a QS bacterium that rapidly causes wilt disease of P. heterophylla. Numerous studies indicated that indirect allelopathy through modifications in soil microbiome induced by root exudates contributes to replant disease in agriculture and horticulture (Li et al, 2014;Chen et al, 2018).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In turn, plants regulate their growth and motility under biotic stress or abiotic stress ( Chakraborty and Newton, 2011 ; Liu et al, 2019b , 2020 ). Continuous monoculture leads to many soil-borne pathogens in the soil and a high biotic stress environment for plants, which leads to an increased incidence of disease ( Lapsansky et al, 2016 ; Zhang et al, 2016 ; Kong et al, 2019 ; Liu et al, 2019a ). In recent years, many researchers have found that the enrichment of beneficial microbes in the soil mediated by pathogen infection can alleviate soil-borne disease and expand plant defensive capabilities ( Elad et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…QS inhibition (QSI) can be achieved via different mechanisms such as inhibition of signaling molecule production, blocking the binding of AHL molecule to the receptors, alteration in the structure of target molecule by enzymes and interrupting the transport facility of the signaling molecule through the membrane channel. Molecules interfering with the QSS have gained importance to develop anti-infective drugs [7][8][9]. Natural compounds from plants as well as microbial sources are highly important to combat microbial pathogenicity especially drug resistant bacteria [10][11][12].…”
Section: Introductionmentioning
confidence: 99%